Afghanistan's prospects. Issue 10 (26th November 2019) - Unknown
Abstract : Afghanistan's prospects, at least for the medium term, appear dismal. To many observers, talks between the United States and the Taliban appear little more than a face-saving device for a future US withdrawal. It is likely that a withdrawal of the majority of US forces would lead to increased factional violence and decreased control by the government – and possibly even its collapse.